Drying of mint leaves in a solar dryer and under open sun: Modelling, performance analyses - Akpinar, E. Kayak (Pergamon-Elsevier Science Ltd, 2010)
In this study was investigated the thin-layer drying characteristics in solar dryer with forced convection and under open sun with natural convection of mint leaves, and, performed energy analysis and exergy analysis of solar drying process of mint leaves. An indirect forced convection solar dryer consisting of a solar air collector and drying cabinet was used in the experiments. The drying data were fitted to ten the different mathematical models. Among the models. Wang and Singh model for the forced solar drying and the natural sun drying were found to best explain thin-layer drying behaviour of mint leaves. Using the first law of thermodynamics, the energy analysis throughout solar drying process was estimated. However, exergy analysis during solar drying process was determined by applying the second law of thermodynamics. Energy utilization ratio (EUR) values of drying cabinet varied in the ranges between 7.826 and 46.285%. The values of exergetic efficiency were found to be in the range of 34.760-87.717%. The values of improvement potential varied between 0 and 0.017 kJ s(-1). Energy utilization ratio and improvement potential decreased with increasing drying time and ambient temperature while exergetic efficiency increased. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Energy; Exergy; Forced drying; Open sun drying; Solar drying; Thin-layer drying models; Mint